Highly sensitive natural rubber/pristine graphene strain sensor prepared by a simple method - Liu, Haijun; Gao, Hanyang; Hu, Guoxin (Composites. Part B, Engineering, 2019)
Uniform dispersion of pristine graphene in polymers has always been a difficulty in the research and industry. In this paper, a simple but effective method was used to uniformly disperse the pristine graphene in NR matrix to prepare an NR/pristine graphene composite. The conductivity of this composite with 5 wt% graphene loading fraction was ∼0.005 S/m, around 4 orders of magnitude higher than that prepared by other methods with a similar loading fraction. The gauge factor (GF) of the strain sensor using the as-prepared composite as the component could be as high as 46, taking a lead positon in the reported strain sensors. Owing to the high sensibility, the sensor was suitable to be used for the detection of very subtle motions such as breathing or heartbeat. In a wrist-pulse testing, premature beats, less forceful heartbeats, and the “P”“T”“D″ waves of the heartbeats could be precisely monitored and distinguished. Swallowing and vocalization could also be efficiently detected by attaching the sensor on the subject's throat. [Display omitted] •Convenient method to uniformly disperse pristine graphene in natural rubber matrix was proposed.•Pressing treatment affected the conductivity and sensitivity of the composite.•The conductivity of composite with 5 wt% graphene loading fraction was around 0.005 S/m.•The GF of the strain sensor was as high as 46.